Ethical Considerations Arising from the Use of Assisted Reproductive Technologies - Klipstein, Sigal (Seminars in Reproductive Medicine, 2012)
The rapid growth of reproductive medicine has in many cases occurred faster than societies have been able to assimilate the changes and incorporate them into the social fabric. Oftentimes, the widespread use of reproductive techniques and fertility-enhancing medications has occurred before the ethical implications of these technologies have been considered. This article introduces ethical concepts that can be used as tools to understand the moral dilemmas inherent in the practice of reproductive medicine. These concepts are then used to form a framework for discussing specific ethically charged issues including the increasing prevalence of multiple pregnancies and the option of multifetal pregnancy reduction, ethical considerations in the prevention of ovarian hyperstimulation syndrome, and access to fertility treatments among different populations. Furthermore, considerations of when to offer these technologies and situations in which care may be refused are discussed. In closing, the role of ethics committees as an approach to navigating difficult clinical situations is introduced.
Keywords: ethics; informed consent; beneficence; justice; autonomy